Women`s Contribution to The Dissemination Of The Book “Sahihul Bukhari” - Odinaxon Muhammad Yusuf (Jurnal Studi Ilmu Alquran dan Tafsir, 2025)
This study explores the significant contributions of women in the transmission and dissemination of Sahihul Bukhari, a revered collection of hadith compiled by Imam Bukhari. The research aims to highlight the roles of female scholars in preserving and teaching Sahihul Bukhari, often overlooked in mainstream Islamic scholarship. Using a qualitative methodology, the study examines historical texts, biographical sources, and scholarly articles, alongside interviews with contemporary female hadith scholars. The findings reveal that women not only studied Sahihul Bukhari but also taught, transcribed, and narrated it across generations. Notable figures such as Karima al-Marwaziyya and Fatima bint Ibrahim ibn Jowhar played pivotal roles in hadith transmission, issuing ijazah (teaching authorizations) and leading study circles. The study also discusses modern institutions continuing this tradition. Despite societal challenges, female scholars have significantly shaped Islamic education. Recognizing their contributions fosters a more inclusive understanding of Islamic scholarship. The study concludes by emphasizing the need for further research and greater recognition of women’s roles in Islamic intellectual history.